2021
DOI: 10.3847/1538-4357/ac2d2e
|View full text |Cite
|
Sign up to set email alerts
|

A Turbulent Heliosheath Driven by the Rayleigh–Taylor Instability

Abstract: The heliosphere is the bubble formed by the solar wind as it interacts with the interstellar medium (ISM). The collimation of the heliosheath (HS) flows by the solar magnetic field in the heliotail into distinct north and south columns (jets) is seen in recent global simulations of the heliosphere. However, there is disagreement between the models about how far downtail the two-lobe feature persists and whether the ambient ISM penetrates into the region between the two lobes. Magnetohydrodynamic simulations sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…Zank et al (2021) studied the interaction and transmission of quasi-2D turbulence through a collisionless perpendicular shock wave in the large beta regime and found that the downstream spectral amplitude is increased significantly. Simulations also demonstrate that a Rayleigh-Taylor-like instability (Opher et al 2021), which mixes the HS and LISM plasmas, can form turbulent heliospheric jets with scales of order 100 au and a turnover timescale of years (Opher et al 2015). How far downstream the turbulence ensues, whether the above processes could further accelerate the PUIs in sufficient numbers, depending on the source of energy, and how these accelerated PUIs get transported further into the HS should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Zank et al (2021) studied the interaction and transmission of quasi-2D turbulence through a collisionless perpendicular shock wave in the large beta regime and found that the downstream spectral amplitude is increased significantly. Simulations also demonstrate that a Rayleigh-Taylor-like instability (Opher et al 2021), which mixes the HS and LISM plasmas, can form turbulent heliospheric jets with scales of order 100 au and a turnover timescale of years (Opher et al 2015). How far downstream the turbulence ensues, whether the above processes could further accelerate the PUIs in sufficient numbers, depending on the source of energy, and how these accelerated PUIs get transported further into the HS should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another important conclusion recently arrived at (Opher et al. 2021 ) is that the kink instability is not the driving mechanism to the instability of the heliospheric jets (as argued in Sect. 8.2 and speculated in Pogorelov et al.…”
Section: The Split-tail Vs Comet-tail Debatementioning
confidence: 93%
“…Opher et al. ( 2021 ) showed agreement of the split-tail model with both V1 and V2 data across the HP and argue that this has to do with reconnection occurring in the flanks, and as such a comet-tail model is not required for observational agreement. Lastly, one cannot say that the split-tail model disagrees with TeV observations given that the split-tail model has not yet been compared with TeV observations.…”
Section: The Split-tail Vs Comet-tail Debatementioning
confidence: 98%
See 2 more Smart Citations